The motorcycle diaries : notes on a Latin American journey - Guevara, Che, 1928-1967 (Ocean Press ; Centro de Estudios Che Guevara, 2004)
A chronicle of the author's seven-month motorcycle journey throughout South America reveals the beginning of his transformation into a dedicated revolutionary.